Surgical technique for venous patch aneurysms with no neck in a rabbit model. (8th February 2017) - Greim-Kuczewski, Kilian; Berenstein, Alejandro; Kis, Sebastian; Hauser, Anna; Killer-Oberpfalzer, Monika
Abstract : Background: Animal experimental studies are crucial for the development of endovascular devices and embolization techniques for intracranial aneurysms. The aim of the study was to describe the surgical creation technique for an aneurysm with a dilated shape and no definable aneurysm neck. The model should be reproducible in size and shape and stay patent over a long period of time. It should constitute a challenge to endovascular therapy and provide a valuable testing environment for new endovascular devices and techniques. Methods: Surgical creation of 30 no-neck aneurysms was attempted in 15 New Zealand White rabbits using a segment of jugular vein, which was transected, longitudinally opened and sutured to the anterior aspect of the common carotid artery. The first 14 aneurysms were used to develop the technique. Once the technique was mastered and the procedure was standardized, 16 consecutive aneurysms were created. For these aneurysms, digital subtraction angiography was employed after a mean of 120 days to confirm size and patency. All aneurysms were evaluated for patency. Results: Overall aneurysm patency was 93%. Three complications occurred, two of which were related to the vascular anastomosis. Angiographic follow-up showed a median (SD) aneurysm base and height of 6.7 (0.76) mm and 3.2 (0.85) mm), respectively. Conclusions: This technique allows creation of aneurysms without a neck which are reproducible in size and shape, and which remain patent. The model contributes to the list of aneurysm models fit for evaluation of embolization devices and techniques. It is particularly useful in exploring treatment options for wide-neck aneurysms and aneurysms which presently do not qualify for conventional coiling.